Impact of war in Ukraine and post-pandemic COVID-19 period on the psychophysiological state of Ukrainian schoolchildren aged 12-13 - Galan, Yaroslav; Moseychuk, Yuriy; Dotsyuk, Lidiia; Kushnir, Iryna; Moroz, Olena; Kurnyshev, Yurii; Duditska, Svitlana; Lohush, Lesia; Kyselytsia, Oksana; Yachniuk, Maxym; Nakonechnyi, Ihor; Predyk, Alina; et al. (My University, 2024)
The article presents a comprehensive analysis of the psychophysical state of schoolchildren, taking into account the chal-lenges posed by the post-pandemic COVID-19 period and the military actions in Ukraine. The study covers the impact of these events on the psychological well-being, physical health, social adaptation and educational achievements of schoolchildren. Using an interdis-ciplinary approach, the article analyses data collected through surveys, interviews, and physical health indicators, as well as psycholog-ical tests, to identify key trends and impacts. Materials and methods.The pedagogical experiment involved 103 schoolchildren aged 12-13 from general secondary education institutions of the Chernivtsi region in the period of the academic year 2023-2024 during various sports, health, recreational, and charity events. Results.The obtained results highlighted the problematic areas related to schoolchil-dren’s psychophysical state caused by the aftermath of the COVID-19 pandemic and military conflict in Ukraine. The difference in physical development between the sexes, which is statistically significant (p<0.05), indicates a critical need to develop individually adapted programmes to promote physical activity among students. The analysis of psychological well-being using the SDQ question-naire showed a high risk of psycho-emotional problems in 51.3% of boys and 37.4% of girls aged 12-13 years, which requires the development of targeted psychological and pedagogical measures. Conclusions. The conducted research indicated existing gaps in the system of modern physical education andthe critical need to integrate methods and approaches aimed at improving the schoolchildren’s psychophysical state against the backdrop of general social unrest.
Keywords: psychophysical stat; schoolchildre; military conflict; COVID-19; post-pandemic period